Hubungan orientasi masa depan, pengetahuan keuangan dan kecerdasan spiritual dengan perilaku perencanaan dana pensiun keluarga - Fina Istiana Sugihartatik (STIE Perbanas Surabaya, 2017)
Retirement is the when someone have entered their old age, physically beginning to weaken and skills that they owned will decline. Individuals want the welfare on retirement. This is about how individuals managing and financial planned. Good behavior planning can begin with apply financial knowledge in the form of activities like to saving or allocated fund. This study aim is to determine the influence of future orientation, financial knowledge and intelligence spiritual on behavior retirement family planning. There are 272 people becomes respondents of this study with criteria they are 25 – 55 years old, they are married or unmarried, they are live in Gresik, Surabaya and Sidoarjo, and have minimum income of four million rupiah per month. The technique to analyze the data use t-test and Multiple Regression Analysis (MRA). The result showed that future orientation, financial knowledge, and intelligence spiritual have a positive significant to conduct behavior retirement family planning.